2019
DOI: 10.1248/cpb.c19-00501
|View full text |Cite
|
Sign up to set email alerts
|

Non-naturally Occurring Helical Molecules Can Interfere with p53–MDM2 and p53–MDMX Protein–Protein Interactions

Abstract: We have discovered that β-amino acid homooligomers with cis-or trans-amide conformation can fold themselves into highly ordered helices. Moreover, unlike α-amino acid peptides, which are significantly stabilized by intramolecular hydrogen bonding, these helical structures are autogenous conformations that are stable without the aid of hydrogen bonding and irrespective of solvent (protic/aprotic/halogenated) or temperature. A structural overlap comparison of helical cis/trans bicyclic β-proline homooligomers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Our initial screening of a library of diverse Abh-AA oligomers revealed that homooligomers as short as the trimer, with a p-bromobenzoyl group at the N-terminal position, showed potent MDM2-and MDMX-antagonistic activities. 9) This result suggested that the hydrophobic surface of the tAbh-AA helix fits well into the MDM2 pocket, blocking the interaction with p53. Due to their high hydrophobicity and relatively small molecular weight (M.W.…”
Section: Introductionmentioning
confidence: 93%
“…Our initial screening of a library of diverse Abh-AA oligomers revealed that homooligomers as short as the trimer, with a p-bromobenzoyl group at the N-terminal position, showed potent MDM2-and MDMX-antagonistic activities. 9) This result suggested that the hydrophobic surface of the tAbh-AA helix fits well into the MDM2 pocket, blocking the interaction with p53. Due to their high hydrophobicity and relatively small molecular weight (M.W.…”
Section: Introductionmentioning
confidence: 93%
“…Protein-protein interaction (PPI) is an important structural point in the process of tumor formation and development and is also one of the di culties in targeted tumor therapy [10]. e development of PPI inhibitors for MDMX and P53 provides a new research direction for the treatment of NSCLC [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Folding of the PPII-like helix was suggested for β-proline oligomers, while substitution and bridging of the pyrrolidine ring provided a certain extent of conformational control . Peptidomimetic properties of bicyclic β-proline homooligomeric derivatives allowed inhibition of p53/MDM2 and p53/MDMX interactions …”
Section: Introductionmentioning
confidence: 99%
“…16 Peptidomimetic properties of bicyclic β-proline homooligomeric derivatives allowed inhibition of p53/MDM2 and p53/MDMX interactions. 17 Recently, we introduced a new protecting-group-free method to synthesize β-proline oligopeptides formally made of chiral 5-arylpyrrolidine-2,4-dicarboxylate structural units. 18,19 A formal chain elongation of β-proline oligopeptidic backbone was performed by step-by-step methodology based on 1,3-dipolar cycloaddition of azomethyne ylides.…”
Section: ■ Introductionmentioning
confidence: 99%